2011
DOI: 10.1002/jqs.1509
|View full text |Cite
|
Sign up to set email alerts
|

Holocene survival of the wild horse in Europe: a matter of open landscape?

Abstract: The wild horse Equus ferus was one of the most frequent species of the Late Pleistocene large ungulate fauna in Eurasia and played an important role in the subsistence of human groups, especially at the end the Late Glacial. It is frequently assumed that E. ferus became extinct in Europe at the beginning of the Holocene because of the development of woodlands and loss of open habitats. Because of its preference for open habitats and in spite of its adaptability, the appearance or disappearance of the wild hors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 47 publications
2
44
0
4
Order By: Relevance
“…The beginning of the Holocene, some 11.7 KYA, indeed came with a reduction of open landscapes in Western Eurasia (Huntley and Webb 1988), and a modification in the distribution range of wild horses (Boyle 2006;Sommer et al 2011;Bendrey 2012). Simulation-based vegetation reconstructions, integrating paleo-environmental data, showed that Box 1.…”
Section: Predomestication Timesmentioning
confidence: 99%
“…The beginning of the Holocene, some 11.7 KYA, indeed came with a reduction of open landscapes in Western Eurasia (Huntley and Webb 1988), and a modification in the distribution range of wild horses (Boyle 2006;Sommer et al 2011;Bendrey 2012). Simulation-based vegetation reconstructions, integrating paleo-environmental data, showed that Box 1.…”
Section: Predomestication Timesmentioning
confidence: 99%
“…, Sommer et al. ). However, records from the Carpathian Basin do not support this scenario, as the abundance of horse remains remained steady throughout successive changes of vegetation.…”
Section: Resultsmentioning
confidence: 98%
“…Sommer et al . () have re‐examined and revised the spatio‐temporal dynamics of horse populations across Europe and the western end of the steppe zone for the early and middle Holocene. They correlated wild horse populations with open rather than closed (wooded) environments.…”
mentioning
confidence: 99%
“…Moving outside of the core steppe zone, we encounter a variety of different habitats: relatively wetter to the north and west, and generally hotter and drier to the south (Bendrey, 2011). Sommer et al (2011) have re-examined and revised the spatio-temporal dynamics of horse populations across Europe and the western end of the steppe zone for the early and middle Holocene. They correlated wild horse populations with open rather than closed (wooded) environments.…”
mentioning
confidence: 99%